2021
DOI: 10.1371/journal.pone.0248015
|View full text |Cite
|
Sign up to set email alerts
|

Resistin is a risk factor for all-cause mortality in elderly Finnish population: A prospective study in the OPERA cohort

Abstract: Objective Resistin is a small, cysteine-rich proinflammatory molecule that is primarily secreted by peripheral blood mononuclear cells and macrophages in humans. Previous studies have shown resistin to participate in various pathological processes including atherosclerosis and cancer progression but not many studies have assessed the role of resistin as a risk factor for all-cause mortality. The objective of this prospective study was to evaluate whether resistin predicts mortality among elderly Finnish people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…The decreased risk of dementia in persons with higher resistin levels may also be explained by a higher risk of mortality in those persons due to other age-related diseases. An increased risk of all-cause mortality, independent of traditional cardiovascular risk factors, was indeed reported by previous studies, suggestively due to the involvement of resistin in inflammatory processes ( 21 ). In the present study, however, resistin was not associated with mortality in a post hoc analysis (data not shown).…”
Section: Discussionsupporting
confidence: 69%
“…The decreased risk of dementia in persons with higher resistin levels may also be explained by a higher risk of mortality in those persons due to other age-related diseases. An increased risk of all-cause mortality, independent of traditional cardiovascular risk factors, was indeed reported by previous studies, suggestively due to the involvement of resistin in inflammatory processes ( 21 ). In the present study, however, resistin was not associated with mortality in a post hoc analysis (data not shown).…”
Section: Discussionsupporting
confidence: 69%
“…To the best of our knowledge, this is the first time that the increased risk of cardiovascular death attributable to resistin has been verified in the general population. Resistin had been pointed out as a risk factor for all-cause mortality in the aged population 9 , but this study included younger people and detected an increase of cardiovascular mortality as an effect of high resistin levels. The inclusion of a younger general population, in which cardiovascular mortality is more relevant than other causes of death, may have helped to detect the risk of cardiovascular death.…”
Section: Discussionmentioning
confidence: 74%
“…However, to date the number of participants and the follow-up time of published studies has been insufficient to detect the effect of resistin on cardiovascular mortality. This had only been detected by studying population groups at high risk of death, either through meta-analysis of patients with cardiovascular diseases over 60 years of age 21 , either by following a cohort of people over 70 years of age 9 , or in patients with diabetes over 60 years of age years 22 . This is the first study to demonstrate the effect of resistin on cardiovascular mortality in the general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistin is found in adipocytes and various cells, including peripheral blood mononuclear cells, macrophages, and bone marrow cells, and is involved in the development of inflammatory conditions in humans. However, in humans, only small amounts of resistin are secreted from adipose tissue (9). But it has been found that with obesity and increased visceral fat, more resistin is expressed in cells in macrophages, liver, spleen, and lungs.…”
Section: Introductionmentioning
confidence: 99%